IMPROVED ANIMAL ROTAVIRUS ISOLATION IN MA104 CELLS USING DIFFERENT TRYPSIN CONCENTRATIONS - Rodriguez, C.a.r.; Brandão, P.e.; Ferreira, F.; Gregori, F.; Buzinaro, M. Da G. [UNESP]; Jerez, J.a. (Instituto Biológico, 2024)
Rotavirus is one of the most important etiological agents in infant gastroenteritis and diarrhea in neonatal animals. The purpose of this study was the optimization of isolation of rotaviruses in MA104 (fetal kidney Rhesus monkey) cells by the comparison of culture, taking into account the number of samples, different treatments with trypsin, number of serial passages, and positivity by polyacrylamide gel electrophoresis (PAGE). Twenty diarrheic fecal samples of calves and piglets from São Paulo, State, Brazil, all positive for rotavirus in ELISA and PAGE, were submitted to four isolation protocols: in treatment 1, the inoculum was left on the monolayer and the maintenance medium was trypsin-free; treatment 2 was the same as treatment 1 except that the inoculum was discarded; in treatment 3 the inoculum was left on the monolayer and the maintenance medium had 5 µg/mL of trypsin; treatment 4 was the same as the monolayer treatment 3, except that the maintenance medium had 10 µg/mL of trypsin. Fifteen samples were successfully isolated, representing an efficacy of 75% (15/20). Treatment 3 was the most suitable because the lower number of serial passages and lower cytotoxity to the cells, with statistical significance (p < 0.001) using Freedman's and Wilcoxon's tests.

Os rotavírus são importantes agentes virais envolvidos nas gastroenterite infantil e da diarréia dos animais neonatos. O objetivo deste trabalho foi otimizar o isolamento de rotavírus levando-se em conta o número de amostras, diferentes tratamentos com tripsina, número de passagens seriadas e monitoramento das mesmas através de eletroforese em gel de poliacrilamida (PAGE). Foram utilizadas 20 amostras fecais diarréicas, positivas para rotavírus por meio de ELISA e PAGE, oriundas de bezerros e leitões, as quais foram submetidas a quatro protocolos usando tripsina. No tratamento 1 o inóculo foi mantido e o meio de manutenção não continha tripsina; no tratamento 2 o inóculo foi dispensado e o meio de manutenção sem tripsina; no tratamento 3 o inóculo foi mantido e o meio de manutenção continha tripsina na concentração de 5 µg/mL; no tratamento 4 o inóculo foi mantido e o meio de manutenção continha tripsina na concentração de 10 µg/mL. Todos os inóculos continham tripsina na concentração de 5 mg/mL. Dentre as amostras estudadas, 15 foram isoladas com sucesso, o que representa uma eficiência de 75% (15/20). Dentre os protocolos, o tratamento 3 foi o que apresentou melhor desempenho, considerando-se o número de passagens seriadas, a ausência de citotoxidade e significância estatística (p < 0,001), quando se aplicou o teste de Freedman e o teste de Wilcoxon.
OTIMIZAÇÃO DO ISOLAMENTO DE ROTAVÍRUS ANIMAIS EM CULTURA DE CÉLULAS DA LINHAGEM MA104 USANDO DIFERENTES CONCENTRAÇÕES DE TRIPSINA
Keywords: Rotavirus; MA104 cells; diarrhea; isolation; trypsin.; Rotavírus; células MA104; diarréia; isolamento; tripsina.